A look at WH-questions in direct and crossexaminations: Authentic vs. TV courtroom language - Chen, Meishan; Reppen, Randi (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2021)
Using a corpus-based register approach, this study explores language use of authentic and TV courtroom discourse through the lens of WH-questions, with a focus on direct and cross-examinations. Results show that in addition to differences as a result of these two discourse settings (i.e., authentic and TV courtroom), WH-questions accomplish different goals across the registers of direct and cross-examinations. For example, WH-questions are avoided in authentic cross-examinations, while in TV courtroom discourse WH-questions are used to engage viewers. Results explore how the different communicative purposes of authentic and TV courtroom settings impact the use of WH-questions in direct and cross-examinations.